A new method for prediction and analysis of heat and mass transfer in the counter-flow dew point evaporative cooler under diverse climatic, operating and geometric conditions. (December 2018) - Wan, Yangda; Lin, Jie; Chua, Kian Jon; Ren, Chengqin
Highlights: A counter-flow dew point evaporative cooler is developed. A new method is proposed to investigate the heat and mass transfer performance. A 2-D CFD model for the cooler is verified with experiments. Distributions of temperature and humidity ratio are studied. Effects of the climatic, operating and geometric conditions are investigated. Abstract: Dew point evaporative cooler, regarded as a zero polluting and energy efficient cooling device, has evolved to be a key technology in air-conditioning systems. The water evaporating process in the cooler is a key performing factor as it leads to the heat sink phenomenon. The cooling effectiveness is dictated by its heat and mass transfer coefficients. The conventional methods (mean temperature difference and integration methods) of obtaining these coefficients have limitations. In this work, a new method to determine these coefficients is proposed. Firstly, a NTU - Le - R model is installed to detect these coefficients. It is based on the outlet data of the dew point evaporative cooler. Next, a two-dimensional computational fluid dynamic model is developed to simulate the evaporative cooling process within the cooler and compute the outlet data for the NTU - Le - R model. Upon validation, results from the computational fluid dynamic model demonstrate close agreement to within ± 6.0 % with results acquired from experiments. Finally, the effects of the various conditions on the heat and mass transfer coefficients, including climatic, operating and geometric conditions, are judiciously investigated. The new proposed method has the capability to capture the essential boundary conditions to precisely obtain the transfer coefficients. In contrast to existing practices that combine the assumption of the Nusselt number under constant surface heat flux or temperature conditions with the Chilton-Colburn analogy. This new method simplifies computation while providing accurate data to realize optimum design of the dew point evaporative cooler.